Supplier's fairness concern regarding order allocation in a supply chain: an experimental examination of multifactor influence. (29th July 2020) - Long, Shangsong; Wu, Runze; Liu, Weihua; Wang, Meili
In order to determine whether the supplier's fairness concern changes with different mechanisms in the order allocation of the supply chain, this paper uses multi-method to explore and verify the theoretical findings. Firstly, this paper presents order allocation game models including two suppliers with fairness concern and one retailer without such concern. The paper considers two scenarios: simultaneous bidding and sequential bidding. We find that different bidding mechanisms cause different levels of inequity aversion, and simultaneous bidding is a better choice for the retailer in terms of higher utility. Secondly, this article designs a behaviour experiment to explore the differences between practice and theory from a statistical perspective. Interestingly, the behavioural experiment has found huge differences between behavioural factors that are not reflected in theoretical models. Inequity aversion behaviours are only influenced by bidding sequence; they are not influenced by gender difference, risk concerns, or emotional diversity.